The Application of Virgin Coconut Oil (VCO) on Dermatitis Patients with Impaired Skin Integrity in Agricultural Areas: A Literature Review - Rizeki Dwi FIbriansari; Siti Eka Yuni; Arista Maisyaroh; Eko Prasetya Widianto (KHD-Production, 2022)
Virgin Coconut Oil is a non-pharmacological therapy that can be applied to overcome the problem of impaired skin integrity. Virgin coconut oil contains antioxidants and is rich in vitamin E. The aim of the review was to determine the effect of VCO on impaired skin integrity in farmers with dermatitis. Initial searches for articles were made on Google Scholar and PubMed. Studies on the application of virgin coconut oil found 2,560 articles/journals but only 8 articles met the search criteria. According to search results, virgin coconut oil therapy can solve the problem of impaired skin integrity. Besides, it is also very important to be applied as a non-pharmacological therapy for farmers who are at risk of contact dermatitis. It is hoped that health professionals can recommend this as a therapy for disease problems related to impaired skin integrity such as dermatitis.